Bicornucandona gen. nov., sp. nov. (Crustacea, Ostracoda) from Finegan Springs (Texas, U.S.A.) - Külköylüoğlu, Okan; Gibson, Randy; Diaz, Peter H.; Colin, Jean-Paul (Zootaxa, 2011)
A new freshwater ostracod genus, Bicornucandona gen. nov. and its type species (Bicornucandona fineganensis sp. nov.) are described from Finegan Springs, Texas, U.S.A. The new genus differs from the related genera in the presence of two horn-like structures on the dorsal margin of the left valve in both sexes. This is also the diagnostic character of the type species. Differences in the structure of the hemipenes and prehensile palps of the male, and the shapes of some other soft body parts also separate this genus from the related species. Taxonomic status of the new genus and species are compared and discussed with both living and fossil relatives.